Touchable topography: 3D printing elevation data and structural models to overcome the issue of scale. (27th January 2016) - Hasiuk, Franciszek; Harding, Chris
Abstract : The fundamental problem of geology is scale. Geological length scales range from angstroms for atoms to thousands of kilometres for planets. Geological processes are often very slow (and geological events so very infrequent). Since the beginning of our discipline, it has been the business of geologists to integrate observations at a variety of length and time scales to answer questions about Earth's history and to make predictions about its future. While this may sound like one of the most academic of pursuits, multi‐billion dollar decisions are routinely made by governments and the largest multi‐national corporations on the basis of geological studies that, for example, model groundwater or petroleum occurrence.